1999
DOI: 10.1007/s10434-999-0756-2
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Metastasis in Patients with Breast Carcinoma Accurately Predicts Immunohistochemically Detectable Nonsentinel Node Metastasis

Abstract: Use of IHC increases the likelihood of detection of NSN metastasis, and the risk of IHC-detected metastasis increases with the size of the SN metastasis and the size of the primary tumor. If SN involvement is micrometastatic (< or =2 mm) or detected by using IHC, tumor cells are unlikely to be found in other axillary lymph nodes in patients with a small primary tumor. The clinical significance of micrometastatic disease in lymph nodes is controversial, and a prospective randomized study is necessary to resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
6

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 16 publications
4
72
1
6
Order By: Relevance
“…20,21 However, in patients with SNs found to be positive by H & E staining or IHC, increased scrutiny of NSNs with IHC and additional sections reportedly results in a 10 -20% increase in the detection of NSN metastasis. 21,22 Of the studies analyzed, five used only H & E staining for the evaluation of NSNs. 6,7,9,11,15 In addition to H & E staining, three studies performed IHC and additional sections on NSNs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 However, in patients with SNs found to be positive by H & E staining or IHC, increased scrutiny of NSNs with IHC and additional sections reportedly results in a 10 -20% increase in the detection of NSN metastasis. 21,22 Of the studies analyzed, five used only H & E staining for the evaluation of NSNs. 6,7,9,11,15 In addition to H & E staining, three studies performed IHC and additional sections on NSNs.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, in patients with H & E-or IHCpositive SNs, increased scrutiny of NSNs with IHC and additional sections is reported to result in a 10 -20% increase in the detection of NSN metastasis. 21,22 Five studies included in the meta-analysis reported the routine use of IHC, three did not routinely use IHC, and in three studies the use of IHC was indeterminate. Including studies that varied with regard to the use of IHC on NSNs appears to decrease the homogeneity of the dataset in the meta-analysis, but excluding studies on this basis would markedly limit the size of the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…SLN biopsy has a low but measurable falsenegative rate. Furthermore, it provides no information about the presence of additional non-SLN metastasis, which may occur in 40% to 70% of cases (12)(13)(14). Newer, more accurate, and less invasive means of predicting ALN metastasis would greatly improve breast cancer patient management and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Furthermore, compared with analysis with hematoxylin and eosin (HE) only in ALND specimen, the use of step sectioning and immunohistochemistry in the SLN results in a more accurate histopathologic examination and is associated with a higher detection rate of micrometastases. 6,7 Although the step sectioning and immunohistochemistry can be routinely applied to evaluate one or a few SLN, the systematic use of these techniques is not feasible in the assessment of ALND specimens because of time and financial constraints. However, the prognostic significance and therapeutic implications of SLN micrometastases in terms of axillary recurrence and long-term survival remain a matter of great debate.8 Therefore, the objective of the present prospective study was to evaluate the long-term disease-free and overall survival of patients with SLN micrometastases in whom a completion ALND was systematically omitted.…”
Section: Introductionmentioning
confidence: 99%